Bacterial variety of fish farms and resistance to antibacterial (Orinoquia, 2014)
Bacterial aerobic gram negative heterotrophic community was isolated from water and sediment to determine the variety and antibacterial resistance during a productive period in which no antibiotics were used in two fish farms of Meta country. Samples were plated on selective medium TCBS Agar, McConkey, Citófaga, Cetrimide and Plate Count Agar toperform bacterial counts with the Technical Analysis of Microbiological ICMSF and the Standard Methods. The different colonies were replicated to each medium biochemical identification BBL-Cristal® commercial kit, and for the study of the six antibacterial resistance was used the procedure described by Kirby -Bauer. The multi - resistance was estimated by the multiple antibiotic resistance index (MAR) and the relative abundance index (RAI) was calculated according to Latorre (2007).19 bacterial strains were identified, six were for Klebsiella pneumoniaeand five Enterobacter sp cloacae, and others: aerouginosa Pseudomonas and fluorescens, Chryseobacterium sp. and gleum, Sphingobacterium multivorum, Serratia marcescens and Tetrathiobacter mimigardefordensis. All isolates were resistant to erythromycin and the highest rate of multi- resistant Enterobacter cloacae presented him with 1.00 and 0.8. The biggestRAI accounted enterobacteria (≥800 cfu/g). Finding six strains of Klebsiella pneumonidae five Enterobacter sp with different resistance rates in both environments analyzed, indicates the great variability of these species. The resistance of all microorganisms to erythromycin, and high MAR Enterobacter show that the use of antibiotics in aquaculture coupled with the high concentration of enterobacter may have adverse environmental impacts that could affect public health.
Keywords: bacterial strains; ponds fish; microorganismos; MAR; RAI